The medial forebrain bundle as a target for deep brain stimulation for obsessive-compulsive disorder. (8th June 2016) - Coenen, Volker A.; Schlaepfer, Thomas E.; Goll, Peter; Reinacher, Peter C.; Voderholzer, Ulrich; Tebartz van Elst, Ludger; Urbach, Horst; Freyer, Tobias
Abstract : Deep brain stimulation (DBS) is a promising putative modality for the treatment of refractory psychiatric disorders such as major depression and obsessive-compulsive disorder (OCD). Several targets have been posited; however, a clear consensus on differential efficacy and possible modes of action remain unclear. DBS to the supero-lateral branch of the medial forebrain bundle (slMFB) has recently been introduced for major depression (MD). Due to our experience with slMFB stimulation for MD, and because OCD might be related to similar dysfunctions of the reward system, treatment with slMFB DBS seams meaningful. Here we describe our first 2 cases together with a hypothetical mode of action. We describe diffusion tensor imaging (DTI) fiber tractographically (FT)-assisted implantation of the bilateral DBS systems in 2 male patients. In a selected literature overview, we discuss the possible mode of action. Both patients were successfully implanted and stimulated. The follow-up time was 12 months. One patient showed a significant response (Yale–Brown Obsessive-Compulsive Scale [YBOCS] reduction by 35%); the other patient reached remission criteria 3 months after surgery (YBOCS<14) and showed mild OCD just above the remission criterion at 12 months follow-up. While the hypermetabolism theory for OCD involves the cortico–striato–thalamo–cortical (CSTC) network, we think that there is clinical evidence that the reward system plays a crucial role. Our findings suggest an important role of this network in mechanisms of disease development and recovery. In this uncontrolled case series, continuous bilateral DBS to the slMFB led to clinically significant improvements of ratings of OCD severity. Ongoing research focuses on the role of the reward system in OCD, and its yet-underestimated role in this underlying neurobiology of the disease.